Co nowego w cholestazie - część 1. Cholestaza z prawidłową aktywnością gamma- glutamylotranspeptydazy - Lipiński, Patryk; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Cholestatic liver diseases remain a major clinical issue for pediatricians. The article constitutes an up-to-date overview on cholestasis with normal serum gamma-glutamyl transpeptidase activity. The authors presented the pathogenicity, clinical presentation, biochemical and molecular diagnostics of the following disorders: citrin deficiency, progressive familial intrahepatic cholestasis type 4, cholestasis associated with FXR mutations, familial hypercholanemia, cholestasis associated with MYO5B mutations (also cholestatic liver disorder in microvillus inclusion disease), ARC syndrome, giant cell hepatitis with autoimmune hemolytic anemia and cortisol deficiency.